Uji Efektivitas Nefroprotektif Ekstrak Buah Kersen (Muntingia Calabura) Terhadap Perubahan Morfologi Ginjal dan Tumor Necrosis Factor-alpha (TNF-ɑ) pada Tikus yang di Induksi Gentamicin - Gracia Indri Perangin-Angin; Asyrun Alkhairi Lubis; Refi Ikhtiari (Journal of Pharmaceutical and Sciences, 2026)
Background: Gentamicin is an effective aminoglycoside antibiotic widely used in the treatment of Gram-negative bacterial infections. However, its clinical use is often limited by nephrotoxicity associated with oxidative stress and inflammatory responses, characterized by increased levels of Tumor Necrosis Factor-alpha (TNF-α) and alterations in renal morphology. Kersen fruit (Muntingia calabura L.) contains various bioactive compounds, including flavonoids and polyphenols, which exhibit antioxidant and anti-inflammatory properties and may provide nephroprotective effects. Objective: This study aimed to evaluate the nephroprotective effect of kersen fruit extract on renal morphological changes and TNF-α levels in gentamicin-induced rats. Methods: An experimental study was conducted using five groups of male rats (n = 5 per group), consisting of a normal control group, a gentamicin control group (100 mg/kg BW), and three treatment groups receiving gentamicin combined with kersen fruit extract at doses of 100, 200, and 400 mg/kg BW, respectively. The observed parameters included macroscopic renal morphology (color, texture, and size) and TNF-α levels. Data were analyzed using One-Way Analysis of Variance (ANOVA) followed by Tukey’s post hoc test at a 95% confidence level. Results: Gentamicin induction caused dark brown discoloration of the kidneys and significantly increased TNF-α levels compared with the normal control group (p < 0.01). Administration of kersen fruit extract demonstrated a dose-dependent tendency to improve renal morphology and reduce TNF-α levels. The most pronounced effect was observed at a dose of 400 mg/kg BW, which resulted in the lowest TNF-α level and renal morphology closest to normal conditions. However, the differences among treatment groups were not statistically significant (p > 0.05). Conclusion: Kersen fruit (Muntingia calabura L.) extract demonstrated potential nephroprotective activity against gentamicin-induced renal injury, as indicated by the tendency to improve renal morphology and reduce TNF-α levels. The dose of 400 mg/kg BW exhibited the most favorable effect among the tested doses. Further studies involving longer treatment durations, larger sample sizes, and additional renal function parameters are required to confirm the nephroprotective efficacy of kersen fruit extract.